Factorial Analysis on Acetic Acid Production Using Banana Stem Waste - Mohd Faizan, Jamaluddin; Jailani, Salihon; N., Zainol (2011)
The performance of acetic acid production using banana stem waste as substrate in anaerobic system was investigated under the conditions of various OLR (1.0 g TS/l.d–7.0 g TS/l.d) and HRT (3 d–15 d). Conditions for OLR and HRT in this study were based on the best range obtained from literature review. Mixed culture for this study was from banana plantation soil and acclima- tized in anaerobic condition. Factorial analysis was applied allowing a screening of the experimental variables organic loading rates (OLR) and hydraulic retention times (HRT). In this work the estimation of the regression coefficients of all models were done using Matlab programming which operates by minimizing the sum of squared differences between the actual and predicted yields. Results from factorial analysis have shown that both variables which were OLR and HRT have significant effect to acetic acid production. The acetic yield is ranging from 487 mg/l to 811 mg/l depending on HRT and OLR value. Acetic acid production was found to be strongly influenced by HRT and OLR. Besides, the types of inoculums and waste used can affect the range of HRT and OLR in production of acetic acid. Increased in HRT and OLR could increased the acetic acid concentration as shown in this study and other researches. The longer period of time and the higher organic loading rate in the reactor may promote microbe growth and high yield of acetic acid.